Higher education management in China under digital transformation - Xuan Wang; Bing Wang (RUDN journal of Sociology)
With the development of information technology, digitalization has become a global trend of social development - technologies and knowledge are updated at an incredible speed. Under digital transformation, universities, as the foundation for training specialists and the engine of scientific-technological progress, should adapt to social changes, keep up with the development of technologies and apply information innovations to improve their management system and human resources. The article presents the general vector of development of the higher education management in China under digital transformation by reviewing its trends in Chinese universities, analyzing their current situation, problems and prospects for introducing digital management elements. Four Chinese higher education institutions of different levels were selected as illustrative cases, and the “typical examples of the development and application of the educational management informatization tools using digital technologies in 2022-2023” prepared by the journal Informatization of Education in China and defined by China’s Ministry of Education were used as the sampling frame. The results of the study showed that under the global digital transformation, Chinese universities have used social resources to complete the upgrade of their information systems, infrastructure, security and safety systems in five key areas, but there are still some challenges. In general, with the information support of the digital management platform, Chinese universities have begun to shift from the experience-based management to the big data-based management.